2021
DOI: 10.34172/ehem.2021.13
|View full text |Cite
|
Sign up to set email alerts
|

Presenting an environmental performance evaluation model for gas refineries: A case study in the South Pars Gas Complex, Iran

Abstract: Background: Controlling and validating the environmental performance of organizations, is a major problem that has been stated in the international standard ISO 14031. The aim of this study was to present a model for evaluating the environmental performance of Iran’s gas refineries using the environmental performance evaluation (EPE) method, based on the operational performance index (OPI) and management performance index (MPI). This case study was conducted in the ninth refinery of the South Pars Gas Complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2121
2121
2121
2121

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The growing expansion of industries and scientific advances has created new horizons of environmental impacts, and different outcomes of health and safety categories are detected each year [34]. As mentioned before, projects of upstream petrochemical industries in the country showed that in previous programs, natural and environmental values had been overlooked [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing expansion of industries and scientific advances has created new horizons of environmental impacts, and different outcomes of health and safety categories are detected each year [34]. As mentioned before, projects of upstream petrochemical industries in the country showed that in previous programs, natural and environmental values had been overlooked [35].…”
Section: Resultsmentioning
confidence: 99%
“…The study population of this research included managers and experts working in different parts of gas refineries with at least 5 years of relevant work experience in HSE (health, safety, and environmental) and manage- [34] ment. The maximum sample was randomly determined 20 people based on the Cochran formula for multicriteria decision-making.…”
Section: The Statistical Community Of Researchmentioning
confidence: 99%